Ontogeny and Sociobiological factors affecting behavior and its repeatability in captive-bred Arctic foxes (Vulpes lagopus) - Seoyun Choi; Kristine Ulvund; Craig Jackson; Arild Landa; Anders Angerbjörn (Behavioral Ecology and Sociobiology, 2026)
Understanding how behavioral variation emerges during early development is essential for interpreting individual differences and their ecological relevance. Early-life behavioral development can involve substantial individual variation shaped by biological and social contexts, resulting in differing levels of repeatability across behaviors. In captive-breeding programs, identifying these developmental patterns and their causes can provide a valuable reference for conservation-relevant species. We studied the ontogeny, individual variation, and repeatability of behavior in 138 captive-born Arctic foxes ( Vulpes lagopus ) in a reintroduction program using repeated focal observations during early and late juvenile periods. Using multivariate Poisson mixed models, we quantified individual- and litter-level variance, assessed temporal and socio-biological influences (i.e., month, sex, sex ratio, litter size), and estimated among- and within-individual behavioral correlations. Juveniles exhibited clear developmental shifts, including reduced play and resting and increased agonistic interactions. Among socio-biological factors, only litter size had a significant effect, with juveniles from larger litters showing elevated vigilance. Crucially, overall repeatability, which incorporates both individual and litter identity, was consistently higher than individual-only repeatability. This divergence indicates that shared early-life environments account for a substantial portion of consistent behavioral variation, whereas individual-level consistency remains comparatively low during the juvenile period. Among-individual correlations were weak, whereas within-individual correlations were stronger for specific behavior combinations. These findings show how early-life behavioral traits are jointly shaped by individual and social factors, clarifying the sources of behavioral variation during development.

That's So Last Season: Unraveling the Genomic Consequences of Fur Farming in Arctic Foxes ( Vulpes lagopus ) - Christopher A. Cockerill; J. Camilo Chacón‐Duque; Nora Bergfeldt; Johanna von Seth; Gabriella Björklund; Malin Hasselgren; Johan Wallén; Anders Angerbjörn; Eva Fuglei; Ester Rut Unnsteinsdottir; Paula White; Gustaf Samelius; et al. (Molecular Ecology, 2025)
Humans have relied on animal fur for centuries, yet fur farming only began recently during the mid‐19th Century. Little is known about this incipient domestication or the genomic processes involved. Domestication may involve founder effects, population bottlenecks and low population size, which, when combined with intense artificial selection, lead to inbreeding, a limited gene pool and reduced fitness. The arctic fox ( Vulpes lagopus ) has been farmed intensively since the early 1900s and has been artificially selected for economic phenotypes. We investigated the origin of these lineages and the genomic consequences of intensive farming by comparing the genomes of farmed and wild arctic foxes from across their range. Our research indicates recent inbreeding through long Runs of Homozygosity and reduced genomic variation in farmed foxes relative to their respective wild populations. We identified a coastal ecotype origin for all Fennoscandian farmed arctic foxes, aligning them phylogenetically with the wild Icelandic population, a geographically isolated and phenotypically distinct coastal lineage. The depleted genome‐wide heterozygosity and increased recent inbreeding in farmed fox lineages is consistent with a heavy consequence of domestication, shedding light on the demographic history and genomic consequences of human manipulation. We highlight the need for increased genomic investigations into fur farm populations to understand the incipient domestication process and uncover the cost of intense farming. The genomic consequences of domestication must be considered in the management of fur farms, with actionable steps needed to prevent descendants of escaped farmed foxes from polluting the gene pool in the wild through introgression.

Fecal glucocorticoid metabolites as an indicator of adrenocortical activity in Arctic foxes (Vulpes lagopus) and recommendations for future studies - Malin Larm; Anne Lene Hovland; Rupert Palme; Anne-Mathilde Thierry; Andrea L. Miller; Arild Landa; Anders Angerbjörn; Nina E. Eide (Polar Biology, 2021)
Measuring fecal glucocorticoid metabolites (fGCMs) is a widely used, non-invasive method for studies of stress in vertebrates. To study physiological responses in wild Arctic foxes ( Vulpes lagopus ) to perceived stressors such as fluctuating food availability, occurrence of competitors and predators and disturbance from human activities, a species-specific physiological validation of a method to evaluate adrenocortical activity is needed. Here we used 15 captive Arctic foxes (both males and females and juveniles and adults) to investigate fGCM concentrations following ACTH injection (physiological validation), or handling alone and compared them with their respective baseline concentrations prior to the treatments. A 5α-pregnane-3ß,11ß,21-triol-20-one enzyme immunoassay measured significant fGCM increases following both treatments. The time lags to reach peak fGCM values were 9.3 ± 1.3 h and 12.8 ± 1.7 h for ACTH and handling treatment, respectively. Concentrations of fGCMs varied a lot between individuals, but not attributed to sex nor age of the foxes. However, we found a negative relationship between boldness and fGCM concentrations. Faecal glucocorticoid metabolites concentrations did not change significantly over a period of 48 h in samples kept at temperatures reflecting winter and summer means. This would allow the collection of samples up to two days old in the wild regardless of the season. We conclude that our successfully validated method for measuring fGCMs can be used as a non-invasive tool for studies exploring various stressors both in wild and captive Arctic foxes.

DNA-Based Individual and Sex Identification from Wolverine (Gulo Gulo) Faeces and Urine - Eva Hedmark; Øystein Flagstad; Peter Segerström; Jens Persson; Arild Landa; Hans Ellegren (Conservation Genetics, 2004)

Colonization History and Noninvasive Monitoring of a Reestablished Wolverine Population - ØYSTEIN FLAGSTAD; EVA HEDMARK; ARILD LANDA; HENRIK BRØSETH; JENS PERSSON; ROY ANDERSEN; PETER SEGERSTRÖM; HANS ELLEGREN (Conservation Biology, 2004)
The southern Norwegian wolverine ( Gulo gulo ) population was considered functionally extinct in the 1960s but has partly recovered in recent years. Proper management of this population is highly dependent on reliable estimates of critical population parameters such as population size, sex ratio, immigration rate, and reproductive contribution from immigrants. We report on a large‐scale population monitoring project assessing these parameters through genetic tagging of individuals, with feces as the source of DNA. Sixty‐eight different individuals were detected among 147 successfully genotyped samples collected in 2000 and 2001. Sixty of these individuals were represented in the 2001 sample, which may be considered a minimum estimate of the population size. Almost 50% of these animals were sampled only once, however, indicating that the true population size may be markedly higher. Accordingly, a capture‐recapture estimate based on the observed resampling rates suggested a population size of 89 wolverines (95% confidence interval [CI]= 74–104), which is approximately 35% higher than an estimate of 64 obtained from the number of active natal dens (95% CI = 46–95; p = 0.08). Indirect estimates of dispersal distances inferred from mother‐offspring relationships suggested that wolverine males have the ability to disperse up to 500 km, a distance exceeding anything previously reported in the literature. Dispersal distances of more than 100 km were detected for females. Bayesian clustering analysis and subsequent assessment of individual relationships suggest that immigrants from northern Scandinavia have contributed and still contribute to the southern Norwegian gene pool, counteracting genetic erosion and reducing the risk of inbreeding depression. Additional sampling efforts will be undertaken during the coming years to allow for observations of population trends, immigration rate, and reproductive variance among individuals. Such data will provide an important basis for the design of an appropriate conservation plan for this small and vulnerable population.